Infantile systemic hyalinosis: A case report - Shivappa, Sanjay Kantharajapura; Murthy, G R Rajashekar; Murthy, D V Venkatesh; Srinivas, S K (Indian Journal of Child Health, 2015)
Infantile systemic hyalinosis (ISH) is a rare, progressive, autosomal recessive disorder characterized by connective tissue involvement as hyaline deposition in the skin, gastrointestinal tract, muscles, glands, and other organs. We report a child with this rare condition presenting with growth retardation, joint contractures, and intractable diarrhea. Though genetically analyzed, ISH still remains as a poorly understood disease raising concerns during diagnosis and treatment.